Frontispiece: Studying the Key Intermediate of RNA Autohydrolysis by Cryogenic Gas‐Phase Infrared Spectroscopy. Issue 19 (24th April 2022) - Greis, Kim; Kirschbaum, Carla; Taccone, Martín I.; Götze, Michael; Gewinner, Sandy; Schöllkopf, Wieland; Meijer, Gerard; von Helden, Gert; Pagel, Kevin
Abstract : RNA In their Communication (e202115481), Kevin Pagel et al. use cryogenic gas‐phase infrared spectroscopy to study the key intermediate of RNA autohydrolysis.